Expression and Purification of the SARS-CoV-2 Nucleocapside (Ncap) in Escherichia coli - Quintero, William E; Lugo, José; Rivas, Keila; Bastidas, Marcos; Cruz, John; Quintero, Militza; Perdomo, Balbino; Castillo, Annie; Rosales, José (Archives of Clinical and Biomedical Research, 2024)
Coronavirus-2 (SARS-CoV-2) causes severe acute respiratory síndrome and causes a global pandemic. Diagnosis of the disease is made through molecular and serological test, wich use SASR-CoV-2 antigens to detect the antibodies present in blood serum. The main antigens used are the spike protein (S) and the nucleocapsid (Ncap). Both proteins are obtanined in expression systems of eukaryotic and prokaryotic cells. In this work, the Ncap was expressed and produced in Escherichia coli, using a low-cost system and with possibilities of producing the antigen on a large scale. The nucleotide sequence was optimized to be expressed in Escherichia coli. After cell lysis, Ncap was located in the insoluble fraction of the cell free extract, forming inclusión bodies. Six consecutives histidines were fused at the C-terminus, wich gave rise the possibility of chemical interaction with divalent metals. The Ncap was therefore purified in immobilized metal affinity chromatography under denaturing conditions and exhibited stability for nine months. The results of the immunoblots with this viral antigen indicated its recognition by the será from patients previously diagnosed with SARS-CoV-2. The banding patterns of the inmunoblots obtained under hybrid conditions suggested proteolytic processing. The present work provides a strategy to produce the Ncap of SARS-CoV-2, with possibility of being used in the diagnosis of SARS-CoV-2.